(untitled) (International Seven Journal of Multidisciplinary, 2024)
Artificial intelligence (AI) has revolutionized the financial sector, especially in the supply and taking of credit. This article looks at how AI can optimize credit analysis, improve risk assessment, and provide a more personalized experience for consumers. Through a literature review and analysis of practical cases, we discuss the benefits and challenges of implementing AI-based solutions in the credit market, highlighting their implications for financial institutions and customers.